PENGARUH STRATEGI PEMBELAJARAN BERDIFERENSIASI TERHADAP MINAT DAN HASIL BELAJAR PESERTA DIDIK - PARLINDUNGAN SITORUS; MARIANA SURBAKTI; PUSPA REALITA GULO (JURNAL PEMBELAJARAN FISIKA, 2023)
This research aims to determine the interests and learning outcomes of students. The research method is quasi experimental design whose research sample is class XI MIPA 2 as an experimental class and the control class, namely class XI MIPA 1. Analysis of learning interest questionnaire data using percentage formulas and learning outcomes are normality test, homogeneity test, hypothesis test, and regression test. The research instrument used observation sheets, study interest questionnaires and multiple-choice questions. The results of the data analysis showed that the average learning interest of experimental class students from the total number of indicators was included in the very high category of 81.25 and the learning outcome data obtained were analyzed using a one-party t-test with Î±= 0.05 obtained tcount = 2.66 and ttable = 1.66 where tcount was greater than ttable which indicated that there was a difference in posttest in the two classes. Differentiated learning strategies are expected to be able to create effective learning and answer the diverse learning needs of students and their potential can develop so that students have freedom in learning. Keywords: differentiated learning strategies, learning interests, learning outcomes.